Improving Students’ Ability to Read and Write Surah At-Tiin through the Implementation of the Problem-Based Learning Model among Elementary School Students - Aristianah Aristianah; Ediansyah Ediansyah (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: The low ability of elementary school students to read and write Surah At-Tiin remains a significant challenge in Islamic Religious Education, as students tend to be less engaged and experience difficulties understanding the material in its context. Objective: This study aimed to improve students’ ability to read and write Surah At-Tiin through the implementation of the Problem-Based Learning (PBL) model among fourth-grade students at SDIT Al-Ihsan Bengkulu Tengah. Method: The study employed a Classroom Action Research (CAR) design conducted in two cycles involving 15 students. Data were collected through observation, tests, and documentation. Results: The findings revealed that implementing the PBL model successfully improved students’ learning outcomes, as indicated by a rise in learning mastery from 13% in the initial condition to 85% in the second cycle. In addition, students became more active, motivated, and collaborative during the learning process. Conclusion: The study concludes that the PBL model is effective in improving students’ ability to read and write Surah At-Tiin. Contribution: This research contributes to the development of more active, contextual, and student-centred instructional strategies in Islamic Religious Education.